Mechanism of Versatile Catalytic Activities of Quaternary CuZnFeS Nanocrystals Designed by a Rapid Synthesis Route. Issue 15 (15th December 2014) - Dalui, Amit; Thupakula, Umamahesh; Khan, Ali Hossain; Ghosh, Tanmay; Satpati, Biswarup; Acharya, Somobrata
<x xml:space="preserve">Abstract</x> Quaternary alloyed nanocrystals (NCs) composed of earth abundant, environment friendly elements are of interest for energy‐harvesting applications. These complex NCs are useful as catalysts for the degradation of multiple refractory organic pollutants as well as nitro‐organic reduction at a rapid rate. Here, a remarkably fast (∼30 s) and facile synthesis of crystalline quaternary chalcopyrite copper‐zinc‐iron‐sulfide (CZIS) NCs is reported. These NCs show excellent catalytic properties by degrading a number of refractory organic dyes and converting nitro‐compounds at a rapid rate. The valence and conduction band information of the newly designed NCs are extracted using scanning tunneling spectroscopy and ultraviolet photoelectron spectroscopy, which reveal energy levels suitable for performing redox chemistry by generating reactive radicals establishing NCs as efficient catalyst with multiple uses. Rapid synthesis of high quality phase‐controlled CZIS NCs with robust catalytic activities could be useful for organic waste treatment.